Prediction of adolescent social anxiety based on parents’ parenting styles - Karimzadeh Navadian, Taha (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Social anxiety is one of the most common anxiety disorders that are influenced by factors such as parenting styles. Parents’ parenting styles play the most important role in raising children. Considering the importance of this issue, the present study was conducted with the aim of predicting social anxiety based on parents’ parenting styles. Methods: This research is of applied type and its method is survey and quantitative in terms of implementation. The statistical population of this research was all male students of the first level of secondary school in Tehran, who were studying in the second semester of the academic year 2014-2016. Considering the size of the population (26600 people) and referring to the table of Morgan and Karjesi, 258 male students were selected as a sample by multi-stage cluster sampling method. The instruments studied were Baumrind’s parenting style questionnaires (1973) and Leibovitz’s social anxiety questionnaire (2003). Data analysis was done using Spss software version 23. Results: Data analysis using Pearson’s correlation coefficient showed that there was a positive and significant relationship between permissive parenting and performance anxiety, as well as between authoritarian parenting and performance anxiety and authoritarian parenting and situational anxiety. There was a positive and meaningful relationship between social groups. In contrast, there was no significant relationship between permissive parenting and social situation anxiety, authoritarian parenting and performance anxiety, and between authoritarian parenting and social situation anxiety. Also, data analysis using multiple regression showed that authoritative parenting style is a negative and significant predictor of social anxiety (P<0.01) and permissive and authoritarian parenting styles are predictive. Social anxiety is positive and significant (P<0.01). Conclusion: According to the findings, it is very necessary to design and hold family education programs and workshops in the field of informing parents about parenting styles and the effect of each of them on their children. It is possible to reduce children’s social anxiety by changing parents’ attitudes and improving family relationships.